On Both Sides of Fiction: Maryna and Serhiy Dyachenko. (1st October 2016) - Ivanova, Ekaterina
Abstract : Ekaterina Ivanova traces the career of Maryna and Serhiy Dyachenko, who have been publishing speculative fiction as a popular team since the 1990s. She notes the ways they undo clichés of the genre, a tendency that has become subtler over time.